2016
DOI: 10.1002/star.201500366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various plasticizers and concentration on the physical, thermal, mechanical, and structural properties of cassava‐starch‐based films

Abstract: The present study investigated the effects of plasticizers (fructose, urea, tri-ethylene glycol, and triethanolamine) with different concentrations on the physical, thermal, and mechanical properties of cassava-starch-based films. The film samples were prepared using casting methods. The moisture content, water solubility, and water absorption of the films increased with increasing plasticizer content. Fructose-plasticized films show excellent water resistance compared to other plasticizers. Film plasticized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 44 publications
(59 reference statements)
11
62
1
5
Order By: Relevance
“…However, at higher starch: glycerol ratio the films were unable to maintain integrity. Similar results for lower solubility at low plasticizer concentration have been reported by Edhirej . According to Gutierrez et al strong hydrogen bond between the hydroxyl groups of starch chains and glycerol molecules decrease sensitivity to water and hence, solubility.…”
Section: Resultssupporting
confidence: 82%
“…However, at higher starch: glycerol ratio the films were unable to maintain integrity. Similar results for lower solubility at low plasticizer concentration have been reported by Edhirej . According to Gutierrez et al strong hydrogen bond between the hydroxyl groups of starch chains and glycerol molecules decrease sensitivity to water and hence, solubility.…”
Section: Resultssupporting
confidence: 82%
“…High values of EB is result of great size of combined plasticizer. Similar results were obtained in the work of Zdanowicz et al Using pure sugars for starch plasticization resulted in brittle materials …”
Section: Resultssupporting
confidence: 89%
“…Similar results were obtained in the work of Zdanowicz et al [12] Using pure sugars for starch plasticization resulted in brittle materials. [6,37] Figure S2 depicts strain-stress curves for TPS films with different LTTM at the same molar ratio of sugar to glycerol. As we can see, TPS/LTTM containing sucrose exhibited the highest TS, YM, and EB and the values were: 5.2 MPa, 293 MPa, and 86.5%, respectively (Table S2, SI).…”
Section: Mechanical Properties Of Tps/lttm Filmsmentioning
confidence: 99%
“…Besides that, as the size of SPNCCs decreased, the percentage of the water absorption also decreased. Additionally, film with big particle size of SPNCCs exhibited greater tendency to absorb water which possibly due to a lower response to stress [33]. In this study, water absorption tests revealed that stabilizing the mixtures with SPNCCs decreased the water absorption capacity.…”
Section: Physical Properties Of Sugar Palm Nanocrystalline Cellulose mentioning
confidence: 59%